The regional counter-blocs strategy in the context of the Middle East Second Cold War (International Journal of Scientific Research and Management (IJSRM), 2021)
Iranian Shiite geopolitical theories aimed at forming a transnational ideological project in order to unite the Islamic world and the formation of Iran military and ideological strategically allies in addition to Iran’s nuclear ambitions have shaken the regional alliances system. Adapting to a radical change in regional policy and security requires the use of a counter-bloc strategy with account for questions regarding the structure, formation, motivation, and risk involved with counter-bloc to Iran. For countries with a Sunni ideology, this stage requires reformulating and upgrading their strategy with a regional ally characterized by hostility to Iran and loyalty to USA, in addition to military, nuclear and cyber capabilities and global support to form a counter-bloc. Israel, a historical enemy of the Arab nation became the best option. Turkey’s absence within this structure may impede the success or continuity of the strategy of the counter-Iran bloc.